The Use of Pyramid Discussion Method to Improve the Students’ Writing Descriptive Text of The Eight Graders in MTSN 1 East Lampung - Sugandi, Bastian; Nurhidayati, Indah; Nuari, Angela Ika Rizky (Yayasan Sembilan Pemuda Indonesia, 2021)
Writing has been one of the four skills that are very important to learn. Writing as a process to get the product is influenced by some elements such as vocabulary, grammar, organization, spelling, and punctuation. In writing English subject is the students have the ability to develop and produce written simple function text in recount text, narrative text, and descriptive text, and report text. Descriptive text is one of the texts that should be mastered by the students of MTsN 1 East Lampung. However, there are many students who ignore to master this skill. This situation results in the students' writing score are still low. Based on the situation, to improve The students' descriptive text, the researcher used Pyramid Discussion in the learning process. Pyramid discussion is one of the methods that is easy and effective to be applied in teaching and learning process in the class. This aim of this research to know whether the use of Pyramid Discussion Method can improve The Students' in writing descriptive in English learning.The result of this research shows that Pyramid Discussion Method had a positive role in improving the descriptive writing ability among The eight graders of MTsN 1 East Lampung. It can be proved by the students' average score from pretest to post-test.